Baroque urbanism in virreynal Lima: to recovery the street of sorrow - Ríos Figueroa, María Esther (2018)
In the search of concrete examples of baroque urbanism between the years 1571 and 1746, we find a particular street called the street of Sorrow (today known as Jr. Camaná), name with which are identified the nine blocks that separate the Great Convent of Saint Dominic of its Recolección. The lack of works of the Baroque Urbanism present divergent opinions about the existence of a baroque urbanism in Lima and in Spanish America. The first to adress the issue was Mattos Cárdenas (1980) who focuses Baroque urbanism, especially in the case of Lima, withhout even mentioning the street of Sorrow. San Cristobal (1986) thinks that there are barely tracks of a properly baroque urbanism in viceregal Lima, and that the baroque expresses itself better in architecture. Other researchers such as Rodríguez Camilloni (1999) affirm that the few examples of baroque urbanism are better found in the XVIII century, for example with the construction of the Navona de Lima (Paseo de Aguas). To explain the process of the street of Sorrow will contribute to shed light on this chapter of the urban historiography and will also entail a better appreciation and recovery of the urban viceregal patrimony of the city of Lima.